2023
DOI: 10.2224/sbp.12462
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Online Class-Related Anxiety and Academic Achievement Among Undergraduates

Abstract: Online classrooms have become an important way to cope with the uncertainty of changing teaching and learning contexts in universities since the outbreak of the COVID-19 pandemic. However, this learning mode has caused new physical and mental health issues, such as online class-related anxiety. We investigated the association between online class-related anxiety and undergraduates’ academic achievement. The results showed that online class- related anxiety had a negative correlation with undergraduates’ academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There is also the difficulty in having access to or connecting with students in the online learning environment, more so, the challenge lies in offering and providing counseling to students remotely and motivating them to participate. Zeng, et al (2023) revealed that undergraduate students suffer from online class related anxiety due to the new setup of learning environment brought by the COVID-19 pandemic. As a result, it affected their academic achievement negatively.…”
Section: The Influx Of Student Concernsmentioning
confidence: 99%
“…There is also the difficulty in having access to or connecting with students in the online learning environment, more so, the challenge lies in offering and providing counseling to students remotely and motivating them to participate. Zeng, et al (2023) revealed that undergraduate students suffer from online class related anxiety due to the new setup of learning environment brought by the COVID-19 pandemic. As a result, it affected their academic achievement negatively.…”
Section: The Influx Of Student Concernsmentioning
confidence: 99%